STUDENT ENROLLMENT ALLOCATION INTO ACADEMIC DEPARTMENTS USING WEIGHTED GOAL PROGRAMMING - Nasruddin Hassan (Pattimura Proceeding, 2017)
A weighted non-preemptive multi-criteria model is built to optimize the distribution of students into academic departments of a faculty by taking into account the limits of space capacity, financial allocation, the number of instructors and affirmative action quotas. Each constraint has a weight attached. This model is applied to the Faculty of Science and Technology, Universiti Kebangsaan Malaysia. The successful application demonstrates the ability of the weighted non-preemptive model to comply with the student intake requirement and constraints of academic departments in the faculty.